Reducing Compressibility of the Expansive Soil by Microbiological-Induced Calcium Carbonate Precipitation - Xiaobing Li; Chunshun Zhang; Hongbin Xiao; Weichang Jiang; Junfeng Qian; Zixiang Li (Advances in Civil Engineering)
Most of the research studies on the improvement of expansive soils are focused on reducing their expansive properties; however, there are few studies on the impact of the soil compressibility after the improvement. In this paper, through indoor high-pressure consolidation tests, the recent microbial-induced calcium carbonate precipitation (MICP) technology is studied to improve the compression characteristics of the expansive soil. The significant effect of different microbial concentrations (achieved by different number of treatments) on the compression deformation is revealed with the hyperbolic function that involves two parameters with clear physical meanings. In particular, after 6 times of treatment with the microbial solution, the compression characteristics of the expansive soil reach the best improvement effect; continuing to increase the number of microbial treatments is, otherwise, not conducive to improving the soil compression performance. Also, a dramatical increase of the structural strength of the microbial-treated expansive soil is presented and investigated. Moreover, we performed a scanning electron microscope (SEM) experiment and confirmed the existence of crystals due to mineralization. This study shows that MICP is an effective and environmentally friendly means of reducing the compressibility of the expansive soil.